Developing and Evaluating a Cloud Service Relationship Theory - Huntgeburth, Jan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book develops, evaluates and refines a cloud service relationship theory that explains how cloud users$1 (Buncertainties arise in these relationships and how they can be mitigated. To that end, the book employs principal-agent theory and the concepts of bounded rationality and social embeddedness. Beyond advancing IS research, the findings presented can greatly benefit governments, IT departments and IT providers, helping them to better understand cloud service relationships and to adjust their cloud service strategies accordingly.s
Introduction -- A Research Framework for Theorizing -- Developing a Cloud Service Relationship Theory -- Evaluating a Cloud Service Relationship Theory -- Summary and Outlook.
Keywords: Economics; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Information Systems and Communication Service; Services